Pengaruh Pengolahan Tanah dan Pemberian Mulsa Jerami Terhadap Pertumbuhan dan Hasil Kedelai - Ella Frisella; Jauhari Jauhari (Universitas Teuku Umar, 2023)
The purpose of this study was to determine the influences of soil processing and giving straw mulch then interaction between these two factors on the growth and yield of soybeans. The first factor were soil processing which consisted of three treatment levels : without tillage, one time tillage, and twice tillage, The second factor were giving straw mulchwhich consisted of three treatment levels: without giving mulch, giving mulch 4 tons per hectare and giving mulch 8 tons per hectare. The number of replicates was three times, there were 9 treatment combinations and 27 experimental units. This study used a factorial Randomized Block Design (RBD). This research had observed there were height plant, fresh and dry weight Stover, number of pods per stalk, dry weight seeds per plot and dry weight 100 soybean seeds. The results showed that Soil Processing and giving straw mulch had a significant effect on soybean growth and yield. The best growth and yields were obtained by twice tillage it was 212.52 g/plot, while due to the application of mulch, the best growth and yields were 8 tones/ha it was 222.12 g/plot. There was no significant interaction between soil processing and giving straw mulch on all observed to the growth and yield of soybeans.